Interactive Karyotyping Training - Ashwin Kotwaliwale (Journal of Krishna Institute of Medical Sciences University, 2013)
Despite the wide use of newer techniques in genetic diagnostics, there remains a need for technologists to learn human chromosome morphology, identify abnormal metaphases and report clinical abnormalities. Global short age of cytogenetic trainers and a time consuming training process makes Karyotyping training difficult. We have developed a web based interactive Karyotyping training tool, KaryoTutor©, that allows technologists to learn karyotyping in an interactive environment and aids the trainer in the training process. KaryoTutor©provides visual clues for identifying abnormal chromosomes, provides instant test scores and includes a reference library of ideograms,sample chromosome images and reference materials. Trainees are able to recursively work on a case till a satisfactory result is achieved,with KaryoTutor providing interactive inputs.Additionally, trainers can assign cases and monitor trainee progress using audit trail management and other administrative features.